Unraveling the fortunes of the fortunate: an Iterative Bayesian Model Averaging (IBMA) approach - Theo S. Eicher; Chris Papageorgiou; Oliver Roehn (Center for Economic Studies and ifo Institute (CESifo), 2007)
We investigate country heterogeneity in cross-country growth regressions. In contrast to the previous literature that focuses on low-income countries, this study also highlights growth determinants in high-income (OECD) countries. We introduce Iterative Bayesian Model Averaging (IBMA) to address not only potential parameter heterogeneity, but also the model uncertainty inherent in growth regressions. IBMA is essential to our estimation because the simultaneous consideration of model uncertainty and parameter heterogeneity in standard growth regressions increases the number of candidate regressors beyond the processing capacity of ordinary BMA algorithms. Our analysis generates three results that strongly support different dimensions of parameter heterogeneity. First, while a large number of regressors can be identified as growth determinants in Non-OECD countries, the same regressors are irrelevant for OECD countries. Second, Non-OECD countries and the global sample feature only a handful of common growth determinants. Third, and most devastatingly, the long list of variables included in popular cross-country datasets does not contain regressors that begin to satisfactorily characterize the basic growth determinants in OECD countries.
Keywords: O40; O47; O51; O52; 330; Wirtschaftswachstum; Regression; Bayes-Statistik; Schätzung; OECD-Staaten; Welt